3D-printed PEEK implant for mandibular defects repair - a new method. (April 2021) - Kang, Jianfeng; Zhang, Jie; Zheng, Jibao; Wang, Ling; Li, Dichen; Liu, Shuguang
Abstract: Functional reconstruction of large-size mandibular continuity defect is still a major challenge in the oral and maxillofacial surgery due to the unsatisfactory repair effects and various complications. This study aimed to develop a new functional repair method for mandibular defects combined with 3D-printed polyetheretherketone (PEEK) implant and the free vascularized fibula graft, and evaluated the service performance of the implant under whole masticatory motion. The design criteria and workflows of the mandibular reconstruction were established based on the requirements of safety, functionality, and shape consistency. Both the biomechanical behavior and the mechanobiological property of mandibular reconstruction under various masticatory motion were investigated by the finite element analysis. The maximum von Mises stress of each component was lower than the yield strength of the corresponding material and the safety factor was more than 2.3 times, which indicated the security of the repair method can be guaranteed. Moreover, the actual deformation of the reconstruction model was lower than that of the normal mandible under most clenching tasks, which assured the primary stability. More than 80% of the volume elements in the bone graft can obtain effective mechanical stimulation, which benefited to reduce the risks of bone resorption. Finally, the novel repair method was applied in clinic and good clinical performances have been achieved. Compared with the conventional fibular bone graft for surgical mandibular reconstruction, this study provides excellent safety and stability to accomplish the functional reconstruction and aesthetic restoration of the mandible defect. Graphical abstract: Image 1 Highlights: A new functional repair method for mandibular defects combined with 3D-printed PEEK implant and fibula graft was proposed. The design criteria and workflows of the mandibular defect repair technology were established. Biomechanical properties of the mandible reconstruction model under whole masticatory motion were evaluated. Good functional and cosmetic outcomes for surgical mandibular reconstruction were obtained.